2013
DOI: 10.1007/s12603-012-0398-0
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition: A highly predictive risk factor of short-term mortality in elderly presenting to the emergency department

Abstract: Malnutrition is the strongest independent risk factor predicting short-term mortality in elderly patients visiting the ED, and it was easily detected by MNA-SF and supported from the ED visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 32 publications
1
40
0
6
Order By: Relevance
“…10,37,64,69,73 Assessing prognostic accuracy for these instruments at different thresholds did not improve on the summary estimates of accuracy from our meta-analysis. In addition, one trial reported sufficient detail to compute interval likelihood ratios (iLR).…”
Section: Screening Instrumentsmentioning
confidence: 59%
“…10,37,64,69,73 Assessing prognostic accuracy for these instruments at different thresholds did not improve on the summary estimates of accuracy from our meta-analysis. In addition, one trial reported sufficient detail to compute interval likelihood ratios (iLR).…”
Section: Screening Instrumentsmentioning
confidence: 59%
“…Increased morbidity, such as infections and poor recovery, compounds the problem of dysphagia in elderly patients with debilitating organic disease. Malnutrition in diseases such as stroke has additionally been shown to have a direct impact on survival (5).…”
Section: Introductionmentioning
confidence: 99%
“…For the MNA‐LF, the ability to predict mortality was described in numerous studies in different settings . Only a few studies have examined the ability of the revised MNA‐SF to predict mortality, with inconsistent results . The ability of either MNA form to predict functional decline is less well studied; investigations using the three categorical classification are lacking.…”
mentioning
confidence: 99%